(untitled) (Zoological Archives: An International Journal, 2022)
Freshwater snails (Gastropoda: families Viviparidae, Physidae, Planorbidae, Lymnaeidae, Melanopsidae, and others) collectively harbour the highest proportion of threatened species among any freshwater invertebrate group globally, yet remain among the least ecologically characterised – limiting the ecological niche models needed to project climate-driven range shifts and prioritise conservation areas. This study presents the first multi-family ensemble ecological niche modelling analysis for European freshwater snails, assembling 184,700 quality-filtered occurrence records for 84 species from 8 families across a 24-country study area, fitting MaxEnt + BRT + GLM ensemble models with 12 predictor variables representing water chemistry, hydrological regime, land use, and climate, and projecting current and future (2070 RCP 4.5 and 8.5) distributions. Current suitable habitat averaged 47,400 +- 24,700 km of river/stream length per species – placing 74.8% of species below the IUCN Vulnerable threshold equivalent for freshwater systems. Under RCP 4.5, mean habitat loss was -28.4% +- 12.4%; under RCP 8.5, -48.4% +- 18.4%. Water temperature increase was the dominant driver of projected habitat loss (partial R2 = 0.54), followed by reduced summer low-flow conditions (0.38). Endemic species restricted to single river basins showed 2.84-fold greater projected habitat loss than widespread species, consistent with the greater exposure of range-restricted specialists. Habitat connectivity analysis identified 247 river segments as high-priority climate refugia, of which only 34.7% have any protected area designation.